Analisis terhadap Putusan Mahkamah Konstitusi Nomor 05/PUU-IV/2006 tentang Pengujian Undang Undang Nomor 22 Tahun 2004 tentang Komisi Yudisial - Suparto, Suparto (Pagaruyuang Law Journal, 2019)
Amendment of the 1945 Constitution gave birth to a new state institution, which called the Judiciary Committee. That entity is being formed to conduct selections to the Supreme Court judge candidates and also to supervise the behaviour of the judges. But along the way, the Supreme Court judges felt that the Judiciary Committee’s supervision is interfering with the independency of the judges. Thus, the Supreme Court judges conducted a judicial review on the Law No. 22 of 2004 and Law No. 4 of 2004. After that, the Supreme Court issued Stipulation No. 05/PUU-IV/2006 with the following points verdicts: a) that constitutional judges are not included in the objects of Judiciary Committee’s supervision, because when the idea to form a judiciary committee occurred, the Constitutional Court itself was yet to be existed. Thus by this premise, the formation of the Judiciary Committee is meant to supervise the judges and the Supreme Court judges; b) Supreme Court judges are objects of Judiciary Committee’s supervision. This is in accordance with the primary purpose of the Judiciary Committee’s formation, which was to supervise the behavior of judges as well as Supreme Court judges; c) the material about the supervision is being annulled since it is not in accordance with the checks and balances principle. The Judiciary Committee is merely an auxiliary state organ which cannot supervise Supreme Court and Constitutional Court as the main state organ. The Constitutional Court Stipulation No. 05/PUU-IV/2006 has the potential to violate the principle of nemo judex idoneus in propria causa, which someone cannot act as a judge for himself.